The Short-Term Effect of COVID-19 on Self-Employed Workers in Canada - Louis-Philippe Beland; Oluwatobi Fakorede; Derek Mikola (Global Labor Organization (GLO), 2020)
Using the Canadian Labour Force Survey, we document the short-term impact of COVID-19 on self-employed individuals in Canada, which we interpret as small business owners. We document an important decrease in business ownership between February 2020 and May 2020 (-14.8 percent for incorporated and -10.1 percent for unincorporated entities). We find a greater decrease in ownership and aggregate hours for women, immi- grants and less educated over the same period. The industries with the largest decrease are in art, culture, and recreation (-14.8 percent); in education, law and social, commu- nity and government services (-13.6 percent); and in sales and service occupations (-12.8 percent).
Keywords: L26; J21; J24; I18; 330; COVID-19; Self-Employed workers; Entrepreneurship; Employment; Labour Force; Hours